Kajian Efektivitas Pembelajaran Fisika Dalam Meningkatkan Technological Literacy Dan Kreativitas Siswa Smp Melalui Implementasi Program Pendidikan Teknologi Dasar (PTD) - T. Chandra, Didi (BERKALA FISIKA, 2010)
This research is part of the development program of Technology Education Association (PTD) in junior high school, conducted to test the effectiveness of the PTD program in improving technological literacy and creativity of students. The study was conducted by comparing the learning of physics topics through dynamic power and non PTD PTD. The research method used was a quasi experimental research design with pretest-posttest matched control group design. The samples were students at two different schools but have the same academic homogeneity, with students in classroom learning physics experiments through PTD while controlling class of students in learning physics through non-PTD. The research instrument in the form of test device used to measure technological literacy, and creativity of students. The results showed convincingly that learning physics through PTD is more effective in improving technological literacy, and creativity of students as compared to learning physics through non-PTD. Keywords: PTD, Technological Literacy, Creativity.